2014
DOI: 10.1177/0971852414544010
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Assessment of Gender and Irrigation Technology in Kenya and Tanzania

Abstract: Rural household economies dependent on rain-fed agriculture are increasingly turning to irrigation technology solutions to counter weather variability, and guard against low crop yields. Organizations too are using market-based approaches to disseminate technologies to smallholder farmers, and although women are among their target group, little is known of the extent to which these approaches are reaching and benefiting them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 19 publications
4
42
0
Order By: Relevance
“…Very few studies explore gendered patterns of irrigation technology adoption and women's ability to benefit from them. The existing research on gender and technology adoption is based in South Asia and sub-Saharan Africa (see, for example, Njuki et al, 2014;Theis et al, 2018). There is no published literature on this topic in the context of the MENA region.…”
Section: Irrigation Gender Norms Technologies and Participationmentioning
confidence: 99%
“…Very few studies explore gendered patterns of irrigation technology adoption and women's ability to benefit from them. The existing research on gender and technology adoption is based in South Asia and sub-Saharan Africa (see, for example, Njuki et al, 2014;Theis et al, 2018). There is no published literature on this topic in the context of the MENA region.…”
Section: Irrigation Gender Norms Technologies and Participationmentioning
confidence: 99%
“…These returns and costs likely will not be the same for all household members. Several studies document important changes in gender roles after a technology has been acquired, including shifting burdens of labor and control over agricultural outputs (e.g., von Braun and Webb 1989;Doss 2001;Njuki et al 2014). However, few studies have examined who bears the costs or controls the benefits of a new technology.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-country study in Ghana and Zambia found that female-headed households adopt small-scale technologies at two-thirds the rate of male-headed households; and that whereas female-headed households are more likely to adopt manual technologies (e.g., buckets, wetlands), maleheaded households are more likely to adopt motor pumps and river diversions (van Koppen et al 2012). Analyzing 2005-2013 sales data from KickStart, a nongovernmental organization (NGO), Njuki et al (2014) find that women made up only 6 percent in Tanzania and 18 percent in Kenya of all buyers of motor pumps. These buyers were rarely women in married households purchasing pumps for their own use, but rather were unmarried women or married women purchasing pumps on behalf of their husbands.…”
Section: Introductionmentioning
confidence: 99%
“…These institutions influence the distribution of resources and people's ability to exercise agency and improve their well-being. For example, social norms governing men's and women's roles in the household and community might prohibit women from engaging in certain activities, like irrigation using manual pumps (Njuki et al 2014).…”
Section: Conceptual Framework: Linkages Between Small-scale Irrigatiomentioning
confidence: 99%